2021
DOI: 10.1038/s41598-020-80360-8
|View full text |Cite
|
Sign up to set email alerts
|

Ion tracks in silicon formed by much lower energy deposition than the track formation threshold

Abstract: Damaged regions of cylindrical shapes called ion tracks, typically in nano-meters wide and tens micro-meters long, are formed along the ion trajectories in many insulators, when high energy ions in the electronic stopping regime are injected. In most cases, the ion tracks were assumed as consequences of dense electronic energy deposition from the high energy ions, except some cases where the synergy effect with the nuclear energy deposition plays an important role. In crystalline Si (c-Si), no tracks have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(35 reference statements)
0
13
1
Order By: Relevance
“…Most recently, in our study of sequential ion irradiation of silicon, the removal of defects has been found after irradiation with a 23 MeV I beam (5 keV/nm). This is in contrast to previous works, whereby track formation in undamaged silicon has been found only after cluster ion irradiations [ 25 , 26 , 27 ]. Thus, the second aim of this work was to investigate Al 2 O 3 , MgO and CaF 2 materials’ behaviour when subjected to sequential heavy ion irradiation.…”
Section: Introductioncontrasting
confidence: 99%
“…Most recently, in our study of sequential ion irradiation of silicon, the removal of defects has been found after irradiation with a 23 MeV I beam (5 keV/nm). This is in contrast to previous works, whereby track formation in undamaged silicon has been found only after cluster ion irradiations [ 25 , 26 , 27 ]. Thus, the second aim of this work was to investigate Al 2 O 3 , MgO and CaF 2 materials’ behaviour when subjected to sequential heavy ion irradiation.…”
Section: Introductioncontrasting
confidence: 99%
“…Another argument that supports this point is that experimentally, amorphization of Si by electronic mechanisms occurs with swift irradiation of heavy ions of considerably greater energy than our 10-keV collision cascades, i.e. tens of MeV [47,48]. Thus, melting (amorphization) of the material via electron-phonon coupling as important as the one we observe with the TTM in scenario 1 is highly unrealistic.…”
Section: Defects and Clusters Evolutionmentioning
confidence: 62%
“…In particular, for ceramics, the theory most commonly used to describe radiation damage is the theory of the formation of so-called thermal bursts or thermal peaks arising along the trajectory of an incident particle, which are accompanied by the appearance of local temperature gradients comparable to the plasma temperature [29][30][31]. The formation of such local regions results in a large number of small point defects capable of making significant changes in the properties of materials, up to the formation of radiation damage, called latent tracks or disordering regions [32,33]. Moreover, if for metals the occurrence and subsequent evolution of radiation damage is well described and has a large number of experimental evidence of the proposed theoretical research, then for ceramics, in particular zirconia, such data are quite small, despite the great interest in this class of ceramics, both from a fundamental and practical point of view.…”
Section: Introductionmentioning
confidence: 99%